Spatial distribution of Ne ions in detached divertor plasmas of JT-60U. (January 2019) - Nakano, T.; Asakura, N.
Highlights: Ne III 4f-5g line is identified in a visible range with sufficiently high intensity. The identification allows to reconstruct Ne III distribution for the first time. Ne III peak stays at the high field side of the X-point in detached and attached phases. C radiative cooling at X-point seems insufficient for detachment onset while Ne is sufficient. Abstract: Ne ion visible spectrum, which is consistent with spectra in VUV ranges, is calculated and synthesised for comparison with experimental spectrum. No spectral lines from highly charged Ne ions are identified but Ne III ( Ne 2 + ) ion is the highest charge which yields spectral lines in the visible range with sufficiently high intensity to be observed. Two-dimensional visible spectroscopic measurement of Ne III 4f-5g line and C IV 3s-3p line with an aid of computer tomography technique provides reconstructed emissivity distributions. Comparison of the emissivity distributions reveals that Ne III emissivity is peaked at the high field side of the X-point and C IV is distributed along the outer divertor leg in the case of inner divertor detachment, showing that Ne III contributes more to radiation around the X-point. In contrast, in the case of attachment, Ne III emissivity is peaked at the high field side of the X-point similarly in the detached case but with lower intensity while C IV emissivity is peaked at the X-point, contributing to the X-point radiation. However, given that the divertor plasma is attached, the cabon radiation is not sufficient for detachment onset.